Réponses

2013-07-31T15:41:37+02:00

1)   (3)² − (3) − 1  =  9 − 3 − 1  =  5

 

2)   5(x − 1/5)  =  4(x + 4)

            5x − 1  =  4x + 16

                     x  =  17

 

3)   3(x − 6)  =  2x + 3

       3x − 18  =  2x + 3

                  x  =  21

 

4)   x + 2/3  =  2x − 1/3

               -x  =  −3/3

                x  =  1

 

5)   −5(−4)  =  20

 

6)   x/2  =  4,5

          x  =  9

 

7)    2(-3)² + (-3)  =  18 − 3  =  15

 

8)   2x − 25  =  3

                2x  =  28

                  x  =  14

 

9)     1 /    2 /     3 / 4 /   5 / 6 /   7 /   8

        5 / 17 /   15 / 1 / 20 / 9 / 15 / 14

        E /  Q  /   U  / A /  T  / I  /  O  /  N